2020
DOI: 10.1111/jocd.13401
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia is associated with androgenetic alopecia in men: A cross‐sectional case‐control study

Abstract: Background Early androgenetic alopecia (AGA) is patterned hair loss occurring before 30 years. Early AGA is frequently reported in men and carries the risk of obesity, metabolic syndrome, and cardiovascular diseases. Hyperuricemia used to be a minor component of metabolic syndrome. Recently, increasing number of studies has proved that hyperuricemia is an independent risk factor for many cardiovascular diseases and psoriasis. However, none of these studies have examined the relationship between hyperuricemia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…Finally, hyperuricemia is an undesirable condition that has been seen as a minor trait of metabolic syndrome, cardiovascular risk, as well as other types of disorders such as psoriasis and alopecia, which have been associated with high levels of blood uric acid ( Guo et al , 2020 ; Ma et al , 2020 ; Talebi et al ., 2020 ; Zhang et al , 2020a ). Even though our criterion for hyperuricemia were defined as blood uric acid >6 mg/dL for women and 7 mg/dL for men, cut-off points could be reconsidered according to the considerations made by Alegría-Díaz et al (2018) .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, hyperuricemia is an undesirable condition that has been seen as a minor trait of metabolic syndrome, cardiovascular risk, as well as other types of disorders such as psoriasis and alopecia, which have been associated with high levels of blood uric acid ( Guo et al , 2020 ; Ma et al , 2020 ; Talebi et al ., 2020 ; Zhang et al , 2020a ). Even though our criterion for hyperuricemia were defined as blood uric acid >6 mg/dL for women and 7 mg/dL for men, cut-off points could be reconsidered according to the considerations made by Alegría-Díaz et al (2018) .…”
Section: Discussionmentioning
confidence: 99%
“…Based on a similar study (4) where the mean± standard deviation was 6.25 ± 1.27 and 5.97 ± 1.15 mg/dl respectively for the case and control group with p<0.001 we calculated the sample size of 104 each in the case and control groups to be necessary for power of 0.8 and α of 0.05.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…Numerous studies have found early-onset AGA to be related with systemic disorders such as obesity (2), hypertension (3), cardiovascular diseases (2) and metabolic syndrome (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…В 2020 году JingwenMa c соавторами в перекрестном исследовании случай-контроль показали следующие результаты: мужчины с АГА (n=1312) имели более высокий средний уровень мочевой кислоты (6,25 мг/дл против 5,97 мг/дл; р <0,001) и более высокую распространенность гиперурикемии (25,0% против 15,6%; р <0,001), чем без АГА (n=2624). Статистически значимой связи между тяжестью AГА и гиперурикемиейне продемонстрировано (р=0,295) [56].…”
Section: андрогенетическая алопеция (ага)unclassified